Efecto de la bioestimulación con micorrizas en el crecimiento, la producción y la calidad nutricional del cultivo de tomate en condiciones de invernadero en Loja. - Morocho Granda, Daniela Guiselle (2025)
Tomato (Solanum lycopersicum) is one of the most important vegetables worldwide. Its intensive production generates a dependence on chemical fertilization, affecting soil and food quality. As an alternative, the use of biostimulants, which have been shown to improve crop growth and quality, is proposed. In this context, the present research aimed to evaluate the effect of biostimulation with mycorrhizae on soil, growth, production and nutritional quality of tomato under greenhouse conditions. The study was carried out at the La Argelia Experimental Farm of the National University of Loja, under a completely randomized design with four treatments in which mycorrhizae were applied at doses of: 25 kg/ha, 50 kg/ha and 100 kg/ha and a control. The application of mycorrhizae significantly improved the amount of mycorrhizae in the soil and decreased soil electrical conductivity. It also improved the growth of tomato plants, increasing root mass weight and plant height in the treatment with 50 kg/ha of mycorrhizae. The number of fruits, fruit weight and yield increased significantly by 75.09%, 60.32% and 61.17%, respectively, with the application of mycorrhizae at doses of 50 kg/ha and 100 kg/ha. Likewise, there was an improvement in firmness, pH and soluble solids content at doses of 50 kg/ha and 100 kg/ha, indicating a higher level of sugars and a better organoleptic quality. Also, vitamin C content increased with the application of mycorrhizae at a dose of 25 kg/ha, protein and days of post-harvest life increased with the application of 100 kg/ha of mycorrhizae. This work demonstrates that the application of mycorrhizae could be an alternative to improve the production and nutritional quality of tomato under greenhouse in Loja.